The development of basic taste sensitivity and preferences in children. (1st August 2018) - Fry Vennerød, Frida Felicia; Nicklaus, Sophie; Lien, Nanna; Almli, Valérie L.
Abstract: This study aims at understanding how preference and sensitivity to the basic tastes develop in the preschool years, and how the two relate to each other. To expand on the existing literature regarding taste preferences conducted in cross-sectional studies, a longitudinal design was applied with children from age four to six years old. During the springs of 2015, 2016, and 2017, 131 children born in 2011 were tested in their kindergartens. To investigate preferences for sweet, sour and bitter tastes, the children performed ranking-by-elimination procedures on fruit-flavored beverages and chocolates with three taste intensity levels. The beverages varied in either sucrose, citric acid, or the bitter component isolone. The chocolates varied in the bitter component theobromine from cocoa and sucrose content. Each year, the children also performed paired-comparison tasks opposing plain water to tastant dilutions at four concentrations. The stimuli consisted of the five basic tastes: sweet (sucrose) sour (citric acid monohydrate) umami (monosodium glutamate), salty (sodium chloride), and bitter (quinine hydrochloride dihydrate). Preference for sweetness levels increased with age, while preference for bitterness and sourness levels were stable. Concerning taste sensitivity, the children showed an increase in sensitivity for sourness and saltiness, a decrease for sweetness, and stability for umami and bitterness. A negative association was found between sweetness sensitivity and preference for sweetness. The study highlights different trajectories of sensitivity and preferences across tastes. On average, a reduction in sweetness sensitivity combined with an increase in preference for higher sweetness was observed from the age of four to six. The weak relationship between taste sensitivity and taste preference in our data suggests that taste preference development is shaped by a multitude of factors in addition to taste sensitivity.